2010
DOI: 10.1007/s10696-011-9074-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of single assembly line for the delayed differentiation of product variants

Abstract: Delayed Product Differentiation (DPD) can reduce the manufacturing complexities arising due to the proliferation of products variety. A new optimization model constructs the optimum layout of delayed differentiation assembly lines for a mix of products to be manufactured by the same system and optimizes the position of the differentiation points. This model employs a classification tool (Cladistics) used in biological analysis and modifies it for use in planning DPD assembly lines configurations in order to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The proliferation of product varieties is mandated by competition and customer demands and is clearly evident in the automotive industry (AlGeddawy and ElMaraghy 2010). As also shown by AlGeddawy and ElMaraghy (2010), this is well demonstrated in the example of car engine accessories where families of products that exhibit wide variety exist; yet they have many common functions, components, and assembly processes.…”
Section: Introductionmentioning
confidence: 82%
“…The proliferation of product varieties is mandated by competition and customer demands and is clearly evident in the automotive industry (AlGeddawy and ElMaraghy 2010). As also shown by AlGeddawy and ElMaraghy (2010), this is well demonstrated in the example of car engine accessories where families of products that exhibit wide variety exist; yet they have many common functions, components, and assembly processes.…”
Section: Introductionmentioning
confidence: 82%
“…For the delayed production mode in process production enterprises, particularly the production of multiple products and different processes, some studies have also considered the impact of PDP in addition to CODP and inventory management. Vanteddu et al [ 35 ] and AlGeddawy et al [ 36 ] studied the location problem of PDP by building models in different scenarios, but mainly for the delayed production of discrete production enterprises.…”
Section: Data Mining To Analyze the Influencing Factors Of Delayed Pr...mentioning
confidence: 99%
“…Part of the literature focused on the positioning of the point of differentiation (POD). In different scenarios, Vanteddu and Chinnam [30], AlGeddawy and EIMaraghy [31], Hsu and Wang [32], Grag and Tang [33], and Lee and Tang [34] studied the positioning of POD or product differentiation point (PDP) in delayed production by building a model. These studies showed that the POD and the PDP are similar in definition and can be collectively referred to as "product differentiation point", which is the starting point of all products in the enterprise or all products in a product category to create a differentiation.…”
Section: Studies On Postponementmentioning
confidence: 99%